On Improvement of the Quality of Forensic Fire Investigations - I. S. Taubkin (Теория и практика судебной экспертизы)
Circumstances having a significant impact on the quality of the conduct of fire investigations in forensic organizations of various agencies are considered. This mainly follows from the shortcomings of inquest and investigation on this category of cases, inadequate number of verified and recommended for forensic practice methods and computer programs, rare use of existing programs, contradictions of legislative acts regulating fire and explosion safety of different objects, from some experts’ insufficient qualification. Absence of data banks on fires and forensic examinations conducted on them as well as of courts’ decisions is common; there is no experimental base to research the fire risk indicators and physical and chemical properties of substances and materials along with the characteristics of their ignition and combustion considering all the conditions of the fire.It is shown that further development of fire forensics and its effectiveness will largely depend on the progress in addressing the aforementioned shortcomings as well as on the success of the academic pursuits and of undertaking the necessary engineering research.